2010
DOI: 10.1088/1009-0630/12/6/09
|View full text |Cite
|
Sign up to set email alerts
|

Reactive DC Magnetron Sputter Deposited Titanium-Copper-Nitrogen Nano-Composite Thin Films with an Argon/Nitrogen Gas Mixture

Abstract: A sintered Ti13Cu87 target was sputtered by reactive direct current (DC) magnetron sputtering with a gas mixture of argon/nitrogen for different sputtering powers. Titanium-coppernitrogen thin films were deposited on Si (111), glass slide and potassium bromide (KBr) substrates. Phase analysis and structural properties of titanium-copper-nitrogen thin films were studied by X-ray diffraction (XRD). The chemical bonding was characterized by Fourier transform infrared (FTIR) spectroscopy. The results from XRD show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, the resistivities of Sm 2 O 3 thin films are much higher than the resistivity of bare n type silicon substrate; this implies that there exists an insulating layer. The conductivity and resistivity are correlated to the scattering from dislocations, impurities inside the crystallite and the potential barrier due to the intra-crystallites boundary effect and scattering through the nano-crystallite boundary [46]. As maintained in XRD and AFM explanation, the crystallinity, grain size and RMS of the deposited films are almost improved with sputtering power and substrate temperature.…”
Section: Electrical Characterizationsmentioning
confidence: 88%
“…However, the resistivities of Sm 2 O 3 thin films are much higher than the resistivity of bare n type silicon substrate; this implies that there exists an insulating layer. The conductivity and resistivity are correlated to the scattering from dislocations, impurities inside the crystallite and the potential barrier due to the intra-crystallites boundary effect and scattering through the nano-crystallite boundary [46]. As maintained in XRD and AFM explanation, the crystallinity, grain size and RMS of the deposited films are almost improved with sputtering power and substrate temperature.…”
Section: Electrical Characterizationsmentioning
confidence: 88%
“…The presence of N neutrals reflected [30] from the single TiCu bi-component surface and impinging on the growing film with sufficient energy (due to large throw distance) can produce atomic scale heating in addition to substrate temperature which decompose the metastable Ti:Cu 3 N nano-crystallites to copper and escaped nitrogen [31]. This phenomenon becomes more significant at substrate temperature of 150˚C), because unbound N atoms out-diffuse from Ti:Cu 3 N crystallite into intercrystallite boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…The refractive index n and the extinction coefficient k as well as the thickness d of polycrystalline nitrided Ti-Cu thin films on thick quartz substrate were studied. They were determined from transmittance data only using PUMA approach and code described by Birgin et al [41] used in our previous work [25,26,31]. Poelman et al [42] have reviewed and tested PUMA approach and shown it to produce excellent estimate of optical constants of thin films.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and increases, as the nitrogen partial pressure ratio increases due to a lower scattering from nitrogen species than that of argon species in plasma during the mass transport between the target and the substrate. Rahmati et al [14][15][16] deposited Ti:Cu 3 N thin films using the reactive DC magnetron sputtering from a Ti 13 Cu 87 target and found that the atomic Ti:Cu ratio in as-deposited thin films (≈ 0.07) was less than that of the original target (≈ 0.15). Also, they indicated a good agreement between experimental results and the T a b l e 2.…”
Section: Determination Of Atomic Ti:cu Ratio Using Sputtering and Mass Transport Considerationmentioning
confidence: 99%